2011
DOI: 10.1177/147323001103900321
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology, Management, Outcomes and Areas for Improvement of Burn Care in Central Malawi: An Observational Study

Abstract: This report describes the epidemiology of burn injuries and quantifies the appropriateness of use of available interventions at Kamuzu Central Hospital, Malawi, between July 2008 and June 2009 (370 burn patients). Burns accounted for 4.4% of all injuries and 25.9% of all burns presenting to the hospital were admitted. Most patients (67.6%) were < 15 years old and 56.2% were male. The most frequent cause was scalding (51.4%). Burns occurred most frequently in the cool, dry season and in the evening. The mean bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
4
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 15 publications
0
41
4
2
Order By: Relevance
“…The higher risk among adult men that has been observed in previous studies from the area regarding severe and fatal burns [8][9][10][11][12]20] was in this setting found in fire burns in younger adult men and in hot liquid burns in older men. The reasons for these gender differences are likely to be multifaceted and connected to different exposures where environment and behaviour interact, falling hardest on men in this resource-constrained setting.…”
Section: Main Findingsmentioning
confidence: 61%
See 1 more Smart Citation
“…The higher risk among adult men that has been observed in previous studies from the area regarding severe and fatal burns [8][9][10][11][12]20] was in this setting found in fire burns in younger adult men and in hot liquid burns in older men. The reasons for these gender differences are likely to be multifaceted and connected to different exposures where environment and behaviour interact, falling hardest on men in this resource-constrained setting.…”
Section: Main Findingsmentioning
confidence: 61%
“…Studies using mortality data [8,9] and those based on inpatient data [10][11][12][13][14] indicate that men are a risk group for burns, as are boys [9,[15][16][17][18]. Inpatient data present gender similarities in Total Body Surface Area (TBSA) burned [11,12,16] and studies considering in-and out-patient data reveal gender similarity in patients of all ages [19][20][21] with a preponderance of boys [22]. On the other hand, studies including all severity levels of burns show higher risks for young and middle-aged women [23] and similar incidence for children [23][24][25] and all ages aggregated [26].…”
Section: Introductionmentioning
confidence: 98%
“…Acute burn diagnosis is complex and studies showed that general clinicians are less accurate than burn experts when assessing both burn size [6][7][8][9] and depth [10,11]. This has been observed in both low-and high-income countries [3,[6][7][8][9][11][12][13].…”
Section: Introductionmentioning
confidence: 97%
“…En la revisión se identificaron dos investigaciones, en la primera se diseñó un dispositivo para la rehabilitación de las personas con enfermedades cerebrovasculares, pero solo tuvo en cuenta la movilidad del brazo, desconociendo el contexto de donde provenían los usuarios [8]. Y la segunda corresponde a un análisis epidemiológico de las lesiones por quemaduras y cuantifica la adecuación de uso de intervenciones disponibles en el Hospital Central de Kamuzu, Malawi, entre julio de 2008 y junio de 2009 [9]. El modelo epidemiológico, que hace parte del pensamiento hipocrático y asume la presencia de enfermos simultáneos con signos y síntomas similares, relacionados con factores ambientales que actúan simultáneamente o no en el estado de salud del individuo.…”
Section: Resultsunclassified